2013
DOI: 10.1111/jbg.12051
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between heritability, genetic correlation and economic weighting in a selection index with and without genomic information

Abstract: The availability of genomic information demands proper evaluation on how the kind (phenotypic versus genomic) and the amount of information influences the interplay of heritability (h(2)), genetic correlation (r(GiGj)) and economic weighting of traits with regard to the standard deviation of the index (σI). As σI is directly proportional to response to selection, it was the chosen parameter for comparing the indices. Three selection indices incorporating conventional and genomic information for a two trait (i … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…The same trend was observed in the present study ( Figure 1 ). Haberland et al (2013) also investigated the significance of the size of the reference population and concluded that N = 1,000 could be considered a minimum size for a reference population in pig breeding.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same trend was observed in the present study ( Figure 1 ). Haberland et al (2013) also investigated the significance of the size of the reference population and concluded that N = 1,000 could be considered a minimum size for a reference population in pig breeding.…”
Section: Resultsmentioning
confidence: 99%
“…where, N is the size of the reference population, and r 2 is the reliability of the GEBV of the animals used in the reference population. In our calculations, we assumed N p = 1,000, which may be considered a minimum for GS in pigs and r 2 was assumed to be 0.49 for all traits ( Haberland et al, 2013 ). The proportion of genetic variance explained by markers ( q 2 ) was assumed to be 0.8 for all breeding goal traits as suggested by Erbe et al (2011) .…”
Section: Methodsmentioning
confidence: 99%
“…where, N is the size of the calibration set and r 2 TI is the reliability of the GEBV of the animals used in the calibration set. In our calculations, we assumed Np = 1000, which can be considered the minimum for GS in pigs (Haberland et al, 2013), while the proportion of genetic variance explained by markers (q2) was assumed to be 0.8 for all breeding goal traits as suggested by Erbe et al (2011). The reliability (r2) was assumed to be 0.5 for all traits.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, scenarios 4 and 5 showed higher accuracy than reference scenarios 1 and 2 when N=1000. Haberland et al (2013) also investigated the effective size of the reference population and found that N=1000 could be considered the minimum size for a reference population in pig breeding.…”
Section: Annual Genetic Gainmentioning
confidence: 99%
“…This approach requires that the correlation between the true value and the GEBV be defined for every genomic trait rGBV, which was accomplished using the approach developed by Erbe et al (2011) based on an equation derived by Daetwyler et al (2008): (1) where, N is the size of the calibration set and r2TI is the reliability of the GEBV of the animals used in the calibration set. In our calculations, we assumed Np = 1000, which can be considered the minimum for GS in pigs (Haberland et al, 2013), while the proportion of genetic variance explained by markers (q2) was assumed to be 0.8 for all breeding goal traits as suggested by Erbe et al (2011). The reliability (r2) was assumed to be 0.5 for all traits.…”
Section: Genomic Breeding Value In Zplan+mentioning
confidence: 99%